1993
DOI: 10.1159/000213508
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's Disease and Ageing: A Chromosomal Approach

Abstract: Alzheimer’s disease (AD) is the most common type of dementia in elderly people. Interrelations between AD and senescence have been the subject of many studies. Some researchers have suggested that chromosomal alterations may be involved in the etiology or pathogenesis of AD. We present cytogenetic findings in patients with Alzheimer’s disease, normal elderly controls and young controls. Aneuploidy, premature centromere division, polyploidy and C-anaphase, were analysed and the results suggest that the cytogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…in peripheral blood lymphocytes, both in AD patients and healthy subjects of same age category. Based on the number of cells with DNA damage and PCD present on any chromosome, the expression of chromosomal instability is more prominent in AD subjects compared to age-matched controls [6,7,8,12,19]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…in peripheral blood lymphocytes, both in AD patients and healthy subjects of same age category. Based on the number of cells with DNA damage and PCD present on any chromosome, the expression of chromosomal instability is more prominent in AD subjects compared to age-matched controls [6,7,8,12,19]. …”
Section: Discussionmentioning
confidence: 99%
“…In Alzheimer's disease, some features of chromosome instability have been shown in the cells of the nervous system [2,3,4,5], but also in cells of peripheral tissues [6,7,8,9]. Aneuploidy as a form of chromosome instability is a relevant factor in neurodegenerative changes in AD and in ageing [2,8,10,11,12,13] with reports that the number of aneuploid neurons in affected brain regions exceed 20% [14]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since MN can contain fragments or whole chromosomes, the application of FISH with the alphoid satellite probe can help to distinguish Previous findings from cytogenetic studies performed to assess chromosomal aberrations in cells of AD patients have been controversial (Ward et al 1979;Nordenson et al 1980;White et al 1981;Kormann-Bortolotto et al 1993). A clear trend of a positive correlation between aneuploidy and both forms of the disease (sporadic and familial) in female AD patients compared with unaffected subjects has been found by Moorhead and Heyman (1983).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in aneuploid metaphases has been reported (Ward et al 1979;Nordenson et al 1980), but not always confirmed (White et al 1981;Kormann-Bortolotto et al 1993).…”
Section: Introductionmentioning
confidence: 95%